PENERAPAN MODEL FLIPPED CLASSROOM-STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Arini Dwi Mayasari; Mohammad Budiyanto; Aris Rudi Purnomo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
This study aimed to describe the increase in student cognitive learning outcomes by implementing flipped classroom-STAD models in the blood circulatory system material. This quantitative study was a pre-experimental design with one group pretest posttest as research design. Samples in this study were 32 students of VIII H class in SMPN 27 Surabaya. Data collection techniques used were test methods given before (pretest) and after (posttest) learning to measure student cognitive learning outcomes and a questionnaire methods to measure learning model implementation. Learning outcomes data were analyzed using paired t-test and N-Gain test. Paired t-test result indicated that there was an effect of treatment on student learning outcomes. As for the N-Gain test result obtained value of 62% that indicated an increase in medium category and classical completeness also achieved with a percentage of 87%. Based on the result, it can be concluded that the flipped classroom-STAD models implementation improved student learning outcomes on science learning in the blood circulatory system material.